Pengaruh Monoklonal Antibodi Bovine Zona Pelusida 3 (bZP3) terhadap Diameter dan Atresia Folikel Ovarium Mencit (Mus musculus) - Annisa Trissatharra; Sri Ratna Dwiningsih; Ratna Sofaria Munir (Majalah Obstetri dan Ginekologi, 2016)
Objectives: To identify the effect of monoclonal antibody bZP3 at ovarian follicles that undergo atresia and diameter of various ovarian follicles.Materials and Methods: This is a true experimental research with post only control group design. Samples were 36 female mices (Mus musculus) which is divided into 6 groups, there are 3 control groups (group 1, 2, and 3) injected by Phospatase Buffer Saline (PBS) 50µl and 3 treatment groups (group 4, 5, and 6) injected by Mab bZP3 50µl. Group 1 and 4 terminated at 5th day, group 2 and 5 terminated at 10th day, and group 3 and 6 terminated at 20th day. Evaluation of atretic ovarian follicles and diameter of ovarian follicles performed by hematoxylin eosin (HE) and the data processed by parametric statistic.Results: There are no significant in different among groups in the aspect of atretic follicles and diameter of folicles (p>0.05), but descriptively, number of follicles undergo atresia of the follicle primary, secondary, and tertiary treatment group was higher than the control group, except on the 20th day of observation time.Conclusion: administration of Mab bZP3 had no effect to amount of atretic follicles and diameter of folicles during observation time.